2022
DOI: 10.1002/1348-9585.12327
|View full text |Cite
|
Sign up to set email alerts
|

Workplace bullying and tiredness at work: A cross-lagged prospective study of causal directions and the moderating effects of a conflict management climate

Abstract: Objectives To prospectively investigate the reciprocal associations between tiredness at work (TAW) and exposure to bullying behaviors and to determine the role of conflict management climate (CMC) as a moderator of these associations. Methods A two‐wave national probability sample of employees in Sweden (18 months between waves, 921 participated at both waves) measuring TAW, workplace bullying, and CMC. Structural equation modelling was used to test four hypotheses abo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…The moderating role of CCM emerges as a pivotal factor in this interplay. CCM pertains to the organization's capacity to effectively address and manage conflicts within the workplace (Rosander and Nielsen, 2022). A positive CCM approach involves fostering open communication, providing supportive mechanisms and implementing appropriate interventions to mitigate conflicts.…”
Section: Moderating Role Of Climate For Conflict Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…The moderating role of CCM emerges as a pivotal factor in this interplay. CCM pertains to the organization's capacity to effectively address and manage conflicts within the workplace (Rosander and Nielsen, 2022). A positive CCM approach involves fostering open communication, providing supportive mechanisms and implementing appropriate interventions to mitigate conflicts.…”
Section: Moderating Role Of Climate For Conflict Managementmentioning
confidence: 99%
“…This can discourage potential bullies from engaging in such behavior as they understand the repercussions for such misconduct. By cultivating a culture that promotes respect, fairness and inclusivity, a strong CCM establishes norms and expectations that discourage bullying, consequently reducing its prevalence and minimizing the risk of WRD among employees (Baillien and De Witte, 2009;Rosander and Nielsen, 2022;Zahlquist et al, 2019). Research by Einarsen et al (2017), which tested HR managers and elected health and safety representatives of Norwegian employees, revealed that the workplace climate strongly influenced the perception on how best bullying cases were managed in the organization.…”
Section: Moderating Role Of Climate For Conflict Managementmentioning
confidence: 99%